2006
DOI: 10.1007/s00424-006-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Chloride and bicarbonate have similar affinities to the intestinal anion exchanger DRA (down regulated in adenoma)

Abstract: DRA (down regulated in adenoma, SLC26A3) is an anion exchanger that mediates electroneutral NaCl absorption in the ileum and proximal colon together with NHE3 (Na/H exchanger isoform 3), and that is involved in duodenal and possibly pancreatic bicarbonate secretion. Thus, its chloride and bicarbonate affinities are important for both processes. [Cl]i and pHi transients were measured using MQAE and BCECF. HEK293 cells stably expressing DRA were exposed to 0 mM Cl at various [HCO3] (9 to 51 mM, at 5% CO2 or 15 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 22 publications
2
46
1
Order By: Relevance
“…These values are then used for the statistical analysis. Using this analytical approach, we have previously obtained evidence that DRA is activated by alkaline pH i (18), a finding that was recently corroborated (39). Regulation of transport activity of DRA may principally occur through changes in V max (by changing the number of DRA molecules in the plasma membrane or by effects on the membrane resident transporter molecules) or by changes of the pH i dependence of the transporter (the so-called set point).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These values are then used for the statistical analysis. Using this analytical approach, we have previously obtained evidence that DRA is activated by alkaline pH i (18), a finding that was recently corroborated (39). Regulation of transport activity of DRA may principally occur through changes in V max (by changing the number of DRA molecules in the plasma membrane or by effects on the membrane resident transporter molecules) or by changes of the pH i dependence of the transporter (the so-called set point).…”
Section: Discussionmentioning
confidence: 62%
“…18, calculates for each individual tracing the initial slope and the maximal change in pH i after change from chloride-containing to chloride-free buffers. These values are then used for the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 DIDS similarly inhibited duct cell HCO 3 Ϫ efflux under basal conditions and in response to stimulation by secretin (12). H 2 DIDS inhibited both basal and secretin-stimulated fluid secretion into Cl Ϫ -rich luminal fluid (17 (35), but Slc26a3-mediated anion exchange with properties of V m sensitivity or electrogenicity was not observed by other laboratories (4,24,28). Moreover, Slc26a3-mediated Cl Ϫ /HCO 3 Ϫ exchange across the apical enterocyte membrane of intact mouse ileum does not exhibit properties of electrogenicity (42).…”
Section: Identification Of Apical CL ϫ /Hcomentioning
confidence: 89%
“…2) (Fig. 2) would favor this model, but Lamprecht et al (27) reported that the presence of even 24 mM luminal HCO 3 Ϫ may increase the K 0.5 of human SLC26A3 for Cl o Ϫ by ϳ10-fold (27). Moreover, the axial distribution of Slc26a3 along the length of the pancreatic duct in any species remains undefined.…”
Section: C297mentioning
confidence: 99%